Effects of regenerative peripheral nerve interface on dorsal root ganglia neurons following peripheral axotomy - Wang, Zheng; Zhang, Dong; Yi, Xin Zeyu; Zhao, Yong; Yu, Aixi (Frontiers in Neuroscience, 2022)
Background: Long-term delayed reconstruction of injured peripheral nerves always results in poor recovery. One important reason is retrograde cell death among injured sensory neurons of dorsal root ganglia (DRG). A regenerative peripheral nerve interface (RPNI) was capable of generating new synaptogenesis between the proximal nerve stump and free muscle graft. Meanwhile, sensory receptors within the skeletal muscle can also be readily reinnervated by donor sensory axons, which allows the target muscles to become sources of sensory information for function reconstruction. To date, the effect of RPNI on injured sensory neurons is still unclear. Here, we aim to investigate the potential neuroprotective role of RPNI on sensory DRG neurons after sciatic axotomy in adult rats. Methods: The sciatic nerves of sixty rats were transected. The rats were randomly divided into three groups following this nerve injury: no treatment (control group, n=20), nerve stump implantation inside a fully innervated muscle (NSM group, n=20), or nerve stump implantation inside a free muscle graft (RPNI group, n=20). At 8 weeks post-axotomy, ipsilateral L4 and L5 DRGs were harvested in each group. Toluidine blue staining was employed to quantify the neuronal densities in DRGs. The neuronal apoptosis index was quantified with TUNEL assay. Western blotting was applied to measure the expressions of Bax, Bcl-2, and neurotrophins (NTs) in ipsilateral DRGs. Results: There were significantly higher densities of neurons in ipsilateral DRGs of RPNI group than NSM and control groups at 8 weeks post-axotomy (p < 0.01). Meanwhile, neuronal apoptosis index and the expressions of pro-apoptotic Bax within the ipsilateral DRGs were significantly lower in the RPNI group than those in the control and NSM groups (p < 0.05), while the opposite result was observed in the expression of pro-survival Bcl-2. Furthermore, the expressions of NGF, NT-3, BDNF, and GDNF were also upregulated in the ipsilateral DRGs in the RPNI group (p < 0.01).